Predicting Failure Modes of RC Beams Strengthening With FRP-NSM System: A Statistical Approach - Ghaidan, Diyaree Jalal; Mohammed, Hasan Jasim; Salahaldin, Ali Ihsan (International Journal of Sustainable Construction Engineering and Technology, 2024)
FRP strengthening using near surface mounted (NSM) is recognized as a highly effective method for strengthening structures using FRP material. However, there are some drawbacks associated with this technique. One of the challenges is concrete cover separation failure, which leads to premature material failure and restricts NSM technique applicability. To address this issue, multinomial logistic regression (MLR) analysis is used. This analysis aimed to investigate the factors (total equivalent steel ratio, stirrup steel ratio, and presence of an anchorage) that can be used to predict the failure modes of reinforced concrete beams strengthened with the FRP-NSM system using a previously published dataset consisting of 99 beam tests from 19 studies. By using odds ratios, which are exponential coefficients, the MLR results were interpreted. The study showed that low TESR and stirrup steel ratio were the major factors leading to flexural failure, FRP bar debonding, and FRP bar rupture compared to concrete cover separation. Moreover, the reinforced concrete beams strengthened with the FRP-NSM system without anchorage had a positive effect on the failure modes, especially with flexural failure and FRP bar debonding compared to concrete cover separation. Based on the classification table analysis, the model’s correct classification rate was 56.6%. The model is accurate in predicting failure modes, as its rate is higher than the chance accuracy rate of 33.7%.